Linguistic creativity and the production of cisheteropatriarchy: A comparative analysis of improvised rap battles in Los Angeles and Cape Town. (January 2018) - Alim, H. Samy; Lee, Jooyoung; Carris, Lauren Mason; Williams, Quentin E.
Abstract: This article presents a comparative analysis of the creative, improvised linguistic performances of gender, race and ethnicity by young men in freestyle rap battles in Los Angeles and Cape Town. Employing a long-term ethnographic, discourse analytic approach, we explore how these improvised verbal duels are both constitutive and transformative of social realities. In particular, we illustrate how Hip Hop emcees creatively perform and are performed into gendered and racialized identities in freestyle rap battles in strikingly similar ways across the Atlantic. While these youth, across both contexts, temporarily transform social meanings attached to race and ethnicity in these verbal duels, a more nuanced examination suggests that they challenge some forms of dominance while (re)producing others. Specifically, it is not simply the case that 'Blackness' or 'Colouredness' is dominant in these improvised interactions, but it is a particular kind of Blackness/Colouredness (masculine, working-class, local, street-affiliated and heterosexual) that both challenges White domination as it marginalizes other classed, gendered and sexualized identities. We conclude by making the link between everyday linguistic creativity and the maintenance/subversion of social categories.